2014
DOI: 10.1002/nau.22707
|View full text |Cite
|
Sign up to set email alerts
|

Results of a prospective, multicenter study evaluating quality of life, safety, and efficacy of sacral neuromodulation at twelve months in subjects with symptoms of overactive bladder

Abstract: Aims: This prospective, multicenter post-approval study evaluated the success rate of sacral neuromodulation (SNM) with the InterStim 1 System at 12-months. Subjects with bothersome symptoms of overactive bladder (OAB) including urinary urge incontinence (UI) or urgency-frequency (UF), who failed at least one anticholinergic medication and had at least one not tried were included. Methods: Subjects with successful test stimulation received an SNM implant. Therapeutic success (!50% improvement in average leaks/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 25 publications
10
87
1
Order By: Relevance
“…The RELAX‐OAB study was a prospective, multi‐center study evaluating the safety and efficacy on the Axonics r‐SNM System, the first rechargeable sacral neuromodulation device with regulatory approval in Europe, Canada, and Australia. The 1‐year data from this study demonstrates positive results in safety and efficacy similar to that in the literature for non‐rechargeable SNM …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The RELAX‐OAB study was a prospective, multi‐center study evaluating the safety and efficacy on the Axonics r‐SNM System, the first rechargeable sacral neuromodulation device with regulatory approval in Europe, Canada, and Australia. The 1‐year data from this study demonstrates positive results in safety and efficacy similar to that in the literature for non‐rechargeable SNM …”
Section: Discussionsupporting
confidence: 81%
“…The cohort of subjects in this clinical study were a moderately to severely affected group with an average of 14.7 voids per day and 9.6 daily incontinence episodes. These baseline symptoms are much more severe than recent trials where the average urgency incontinence episodes ranged from 3.1‐5.2 per day . The dramatic reduction in symptoms seen at 3‐months in the RELAX‐OAB study has been maintained out to 1‐year with 94% of test responders having continued therapy success, and all subjects maintaining a 72% success rate.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Sacral nerve stimulation (SNS) (InterStim, Medtronic, Minneapolis, Minnesota, USA) has been used to treat urologic conditions (overactive bladder and nonobstructive urinary retention) in the United States since 1997 [10,11]. Although initial studies on the use of SNS for fecal incontinence were published in 1995, this therapy did not receive FDA approval for this indication until 2011.…”
Section: Sacral Neuromodulationmentioning
confidence: 99%
“…Recent studies have shown the rate of removal due to infection is 3%. 44 Re-operation for lack of efficacy over time, uncomfortable stimulation, and pain at the generator site are all potentially necessary if the problems cannot be improved by reprogramming. Frequent reprogramming may be required for some patients, …”
Section: Risks and Side Effectsmentioning
confidence: 99%